AN ANALYSIS OF ENGLISH AND INDONESIAN IDIOMS AND PROVERBS - Syarfuni (Getsempena English Education Journal, 2014)
This study described a study about an analysis of English and Indonesian idioms and proverbs. This research purposed to analyze the differences and similarities between English and Indonesian idioms and proverbs that used in daily life. Idiom is a set of word that have different meaning from the basic word. Proverb is a speech that can be used in everyday life for many situation that containing parable, comparison, and advice to that can apply as the way of life. The researcher used some research methodology such as research design, source of data, collecting data, data analysis and research instrument. The methodology of this study is library research. Based on researcher analysis English and Indonesian idioms and proverbs actually almost the same in meaning, but they have their own culture to deliver ideas about idioms and proverbs. It is misunderstanding among the people when they have to deliver the proverb in different culture and socities. So the writer concluded that there are similarities and differences between idioms and proverbs of English and Indonesian but it is depended on their culture.